Vocalization of Western Tarsier (Cephalopachus bancanus Horsfield, 1821) in Bangka Island, Indonesia - Indra Yustian; Dedek Kurniawan; Zahrial Effendi; Doni Setiawan; Enggar Patriono; Laila Hanum; Arum Setiawan (Journal of Tropical Biodiversity and Biotechnology, 2021)
Every tarsier species performs different vocalization behaviour. Cephalopachus bancanus as one of the tarsier species listed as vulnerable in the IUCN red list has limited and different information about their vocalization. This research was designed to explore the species vocalization in the vicinity of Petaling Village, District of Bangka, Bangka Island, Indonesia. Tarsier vocalization inside temporary enclosures was recorded using a handy recorder and analysed using bioacoustics software Audacity 2.3.3 and Raven Pro 1.6.1. We described seven vocalization types with different functions and spectrogram patterns. One type of vocalization, squeak, is produced only by the infant. Two types of vocalizations (whistle and cheeps) were produced by the infant and adult, and four vocalization types were performed by adults. Those types of vocalizations can be heard within human hearing. Some types of vocalizations have peak frequencies at the ultrasonic level, i.e.: agonistic scream, alarm call, distress call, and hysteresis.